2022
DOI: 10.31557/apjcp.2022.23.8.2813
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety Symptoms in Women Newly Diagnosed with Breast Cancer in Kazakhstan and Its Associated Factors

Abstract: Introduction:Diagnosis of breast cancer is associated with high psychological distress. There is a lack of studies examining the prevalence of anxiety among newly diagnosed breast cancer patients in Kazakhstan. Objective: This study aims to assess the mean prevalence and associated sociodemographic and clinical factors of anxiety symptoms in women newly diagnosed with breast cancer. It also aims to determine independent predictors of anxiety risk. Methods: An analysis of 162 newly diagnosed breast cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…It is more likely that female cancer patients will suffer from depression as they are more susceptible to it [ 10 ]. Studies on breast, cervical, and ovarian cancer patients showed that those patients had a high prevalence of depression and anxiety disorders [ [11] , [12] , [13] , [14] ]. Nevertheless, depression is often neglected, and the majority of cancer patients do not receive adequate treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is more likely that female cancer patients will suffer from depression as they are more susceptible to it [ 10 ]. Studies on breast, cervical, and ovarian cancer patients showed that those patients had a high prevalence of depression and anxiety disorders [ [11] , [12] , [13] , [14] ]. Nevertheless, depression is often neglected, and the majority of cancer patients do not receive adequate treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%